A Second Order Characteristic Method for Approximating Incompressible Miscible Displacement in Porous Media - Tongjun Sun; Keying Ma (International Journal of Mathematics and Mathematical Sciences)
An approximation scheme is defined for incompressible miscible displacement in porous media. This scheme is constructed by two methods. Under the regularity assumption for the pressure, cubic Hermite finite element method is used for the pressure equation, which ensures the approximation of the velocity smooth enough. A second order characteristic finite element method is presented to handle the material derivative term of the concentration equation. It is of second order accuracy in time increment, symmetric, and unconditionally stable. The optimal L2-norm error estimates are derived for the scalar concentration.